Unveiling frailty: comprehensive and sex-specific characterization in prematurely aging PolgA mice - Yılmaz, Dilara; Singh, Amit; Wehrle, Esther; Kuhn, Gisela A.; Mathavan, Neashan; Müller, Ralph (Frontiers in Aging, 2024)
Frailty, a geriatric syndrome, is assessed using the frailty phenotype (FP) and frailty index (FI). While these approaches have been applied to aging mice, their effectiveness in prematurely aging mouse models such as PolgAD257A/D257A (PolgA) has not been completely explored. We demonstrated that frailty became evident in PolgA mice around 40 weeks, validated through body weight loss, reduced walking speed, decreased physical activity, and weaker grip strength. Moreover, we also identified sex differences in these mice with females exhibiting slightly more physical decline compared to males. Frailty prevalence in PolgA mice at 40 weeks parallels that observed in naturally aging mice at 27 months and aging humans at 65–70 years. These findings contribute to understanding frailty onset and sex-specific patterns in this prematurely aging mouse model, emphasizing the significance of the PolgA mouse model in investigating aging and related disorders.